Numerical Simulation Research of Smooth Wall Blasting Using the Timing Sequence Control Method under Different Primary Blast Hole Shapes - XinPing Li; JunLin Lv; JunHong Huang; Yi Luo; TingTing Liu (Shock and Vibration)
To make sure the integrity and stability of surrounding rock structure during blasting excavation of important structural planes in deep underground caverns, two kinds of fine blasting methods, timing sequence control fracture blasting network and notch blast hole, are innovatively combined and the formation of cracks between smooth blasting holes with different delay initiation and different shapes of primary blast holes (PBHs) are compared and analyzed. The results show that when the delay initiation time between the successive explosion holes is greater than or equal to the transverse wave of the PBH propagates to the target blast hole (TBH), the concentrated stress along the connection direction of the hole on the wall of the TBH is larger than the other directions of the hole wall. After the TBH is detonated, cracks will preferentially expand along the connection direction of the blast holes. If the PBH is the notch blast hole, more explosive energy will be directed to the wall of the TBH so that the hole wall along the connection direction of the blast holes will be subjected to greater tension stress before the initiation of the TBH. In this way, the interval between successive holes can be increased and the efficiency of blasting excavation of rock mass can be improved accordingly.